Antibacterial Activity of Cacao (Theobroma Cacao Linn.) Pulp Crude Extract Against Selected Bacterial Isolates - Panganiban, Citadel A.; Reyes, Redencion B.; Agojo, Ivy; Armedilla, Rhona; Consul, Jazel Zabrine; Dagli, Hazel Frances; Esteban, Lorwin (JPAIR Multidisciplinary Research, 2010)
Cacao (Theobroma cacao Linn.), a plant with great perennial leaves and yellow or reddish flowers is reported to be antiseptic, diuretic, ecbolic (promotes labor by stimulating uterine contractions), emmenagogue (promotes or stimulates menstrual flow), and parasiticide, Cacao is a folk remedy for alopecia, burns, cough, dry lips, eyes, fever, listlessness, malaria, nephrosis, parturition, pregnancy, rheumatism, snakebite, and wounds. With its wide range of medicinal values, its activity against selected bacterial isolates will be determined in order to find alternative substances that will prevent the widespread of bacterial infection. This study used the experimental research method to determine the antibacterial activity of cacao (Theobroma cacao Linn.) pulp crude extract against selected bacterial isolates including Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853 using the paper disc diffusion method. The Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and the biological stability of cacao against the test microorganisms were also determined using the tube dilution method. Stability tests were also performed such as the determination of the effects of pH and temperature on the activity of cacao against bacterial isolates.
Keywords: Cacao; Theobroma cacao; Bacterial Isolates